2017
DOI: 10.1016/j.imr.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of ultrasound-assisted extraction of glycyrrhizic acid from licorice using response surface methodology

Abstract: BackgroundThe present study optimized ultrasound-assisted extraction conditions to maximize extraction yields of glycyrrhizic acid from licorice.MethodsThe optimal extraction temperature (X1), extraction time (X2), and methanol concentration (X3) were identified using response surface methodology (RSM). A central composite design (CCD) was used for experimental design and analysis of the results to obtain the optimal processing parameters.ResultsStatistical analyses revealed that three variables and the quadra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Adsorption is spontaneous and exothermic, and is expected to decrease with temperature increase. However, studies have also found the opposite or no relationship between changes in temperature and the amount of adsorbed substance [ 30 ]. Studies on the effect of temperature on 2,4-D adsorption using activated carbon have reported that surface activation and the breaking of existing bonds causes new active sites on the carbon surface, thereby increasing its adsorption efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Adsorption is spontaneous and exothermic, and is expected to decrease with temperature increase. However, studies have also found the opposite or no relationship between changes in temperature and the amount of adsorbed substance [ 30 ]. Studies on the effect of temperature on 2,4-D adsorption using activated carbon have reported that surface activation and the breaking of existing bonds causes new active sites on the carbon surface, thereby increasing its adsorption efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…This technique has great extraction efficiency due to the acoustic cavitation effects that occur in the solvent by ultrasonic waves, and this depends on ultrasonic properties, product characteristics, and ambient conditions. With increasing ultrasonic power, the cavitation effect increases the release of the analyte from the sample by providing better penetration of the solvent into the sample (Jang et al, 2017). On the other hand, ultrasonic power boosts can also hinder the release of bioactives from the cells, thus preventing an increase in yield during extended extraction (Vilkhu et al, 2008;Guo et al, 2019).…”
Section: Ultrasound Extraction Using An Ultrasonic Processormentioning
confidence: 99%
“…ANOVA output for Y1 and Y2 is provided in Tables 3 and 4, respectively. ANOVA gives us the information about the level of significance in terms of p-value which should be less than 0.05 for a term to be significant [23]. It is observed that all the linear terms viz.…”
Section: Development Of Regression Model and Statistical Analysismentioning
confidence: 99%